Seni Mural Sebagai Media Pendidikan Seni Rupa: Mendorong Kreativitas dan Penyampaian Ekspresi Siswa. - Fahmi, Khairul (Gayaku Publisher, 2024)
Mural analysis as a means of character education at an early age is an effective and creative effort. Murals, paintings or paintings on walls, can teach positive values and character to children. This article outlines how murals can be used in character education, including teaching positive values, providing real examples, developing creativity, strengthening school identity, addressing social problems, and enhancing independence. A mural drawing on the theme